Comparison between imported versus domestic drug‐eluting stents in China: A large single‐center data. (2nd July 2017) - Liu, Ru; Gao, Zhan; Chen, Jue; Gao, Lijian; Song, Lei; Qiao, Shubin; Yang, Yuejin; Gao, Runlin; Xu, Bo; Yuan, Jinqing
Abstract : Background: In recent years, most drug‐eluting stents (DESs) were domestically produced in China, but how domestic DESs perform compared to imported DESs was still unknown. Methods: A total of 9011 consecutive cases with DESs implantation in a single center throughout 2013 were prospectively collected. Two‐year clinical outcomes were evaluated between patients implanted with imported and domestic DESs. Results: During 2‐year follow‐up, the rates of all‐cause death, cardiac death, myocardial infarction, stroke, and stent thrombosis were not significantly different between two groups. However, the rate of revascularization was significantly higher in domestic DES group, shown as higher rates of overall revascularization, target vessel revascularization (TVR), and target lesion revascularization (TLR) (9.7% vs 6.4%, P < 0.001; 5.6% vs 3.2%, P < 0.001; 4.5% vs 2.2%, P < 0.001, respectively). Accordingly, major adverse cardiac events (MACE) rate was significantly higher in domestic DES group (12.1% vs 8.5%, P < 0.001). Multivariable Cox regression analysis indicated that domestic DES was an independent risk factor of MACE (HR [95%CI]: 1.22 [1.05‐1.41]), overall revascularization (HR [95%CI]: 1.29 [1.09‐1.53]), TVR (HR [95%CI]: 1.54 [1.22‐1.94]), and TLR (HR [95%CI]: 1.85 [1.41‐2.42]). After propensity score matching, the rates of overall revascularization, TVR, and TLR were still significantly higher in domestic DES group, and domestic DES was still predictive of overall revascularization, TVR, and TLR in multivariate Cox regression analysis. Conclusions: Domestic DESs showed the same safety as imported DESs in this real‐world cohort. But, patients implanted with domestic DESs had a higher risk of revascularization than imported DESs.